Pengaruh strategi pembelajaran problem solving berbantuan media dan ceramah dan self-concept terhadap hasil belajar matematika - Sulastri Sulastri; Cecep Anwar Hadi Firdos Santosa; Endang Wahyuningrum (IICET (Indonesian Institute for Counseling, Education and Therapy), 2022)
The purpose of this study is to analyse the effect of the interaction of problem-solving learning strategy with media-assisted and self-concept on the mathematical learning outcomes of elementary school students. This research was conducted at SDS Islam Miftahul Jannah, Cikupa, Tangerang, on the fifth-grade students with 90 population. While the number of samples in the research are 60 students, that consisted of 30 students from V-A (experimental 1) and 30 students from V-B (experimental 2). The research subjects are taken based on classes that have been formed and it is believed that the classes are equivalent. The research method used is an experiment with the research hypothesis testing technique by using two-way ANAVA with factorial 2 x 2. The results of the research showed that the students mathematical learning outcomes that taught by using problem solving learning strategy with media-assisted and lectures are significantly different. There are differences in mathematical learning outcomes of students who have positive self-concept and negative self-concept that taught by using problem solving learning strategy with media-assisted and lectures, it means that H0 is rejected and Hα is accepted. There is no interaction between the use of media-assisted problem-solving learning strategies and self-concept toward students learning outcomes. Based on this research, the teachers are expected to apply problem solving learning method with media-assisted in teaching mathematic and improve students’ self-concept.